Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1007/s004150200008
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and health-related quality of life in a well-defined subgroup of patients with partial epilepsy

Abstract: To investigate the extent and nature of the objective and subjective cognitive deficits and health-related quality of life (HRQOL) in adult outpatients with relatively well-controlled partial epilepsy without symptomatic aetiology, who were on carbamazepine (CBZ) monotherapy. Furthermore, we studied the influence of the epilepsy history and medication on various cognitive functions and the HRQOL. 56 outpatients (29 male, 27 female, mean age 41.3 years) with partial epilepsy were compared with 56 age-, gender-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
4
15
3
Order By: Relevance
“…These findings are consistent with previous research that failed to find severity of epilepsy predicted PWE who had died as a result of suicide [30,31]. Overall, our results are also consistent with findings that patients with well-controlled epilepsy report similar levels of reduced health-related quality of life as those with refractory conditions [32,33].…”
Section: Comparisons Of Patients With Well-controlled Versus Refractosupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are consistent with previous research that failed to find severity of epilepsy predicted PWE who had died as a result of suicide [30,31]. Overall, our results are also consistent with findings that patients with well-controlled epilepsy report similar levels of reduced health-related quality of life as those with refractory conditions [32,33].…”
Section: Comparisons Of Patients With Well-controlled Versus Refractosupporting
confidence: 94%
“…Although the fifth study utilized a diagnostic interview to identify depression, it is now quite dated, and only had a limited sample size of participants (n=88) recruited from general practice [3]. With newer treatment options, Epilepsy & Behavior 26 (2013) [29][30][31][32][33][34][35] therefore, it remains unclear whether this much-cited assumption, that people with refractory epilepsy have higher rates psychopathology in comparison with those whose epilepsy is well-controlled, is supported by sufficient evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as demonstrated by Ryan et al [9], the HRQOL of epileptic patients is more influenced by the self-perception of stigma than by the history and medication-related variables of the disease. Similar findings as ours, on the impact of epilepsy history variables to the HRQOL outcome, were presented in the Engelberts et al study [3].…”
Section: Discussionsupporting
confidence: 89%
“…Our results clearly differ from those reported by Jacoby [6] and Aldenkamp et al [1] and are similar to those reported by Engelberts et al [3]. In the latter patients with partial epilepsy even when able to maintain regular jobs, had impaired cognition and HRQOL.…”
Section: Discussionsupporting
confidence: 68%
“…Depending on disease severity and seizure frequency, cognitive dysfunction can cause intellectual decline, reduced information processing speed, memory impairments, and attention deficits [58, 59]. Patients with epilepsy can struggle with this dysfunction their entire life because it can affect their education as a child, their social development as they grow older, and their future employment as an adult [49].…”
Section: Discussionmentioning
confidence: 99%